Catholic Institutions of Higher Education and K-12 Schools Partnering for Social Justice: A Call for Scholarship - Whipp, Joan L.; Scanlan, Martin (Catholic Education: A Journal of Inquiry and Practice, 2009)
This article calls for scholarship on emerging partnerships between Catholic institutions of higher education and Catholic K-12 schools that aim at socially just schooling. Justice, ethical care, learning, and social entrepreneurship are explored as possible conceptual frameworks for this research.